Copelatus Erichson, 1832 from Maharashtra, India, with description of three new species and notes on other taxa of the genus (Coleoptera: Dytiscidae: Copelatinae) - Sheth, Sayali D.; Ghate, Hemant V.; Hájek, Jiří (Zootaxa, 2018)
The Copelatus species occurring in Maharashtra State, India, are reviewed. Altogether, nine species are recorded, three of which are described as new: Copelatus deccanensis sp. nov. (C. nigrolineatus species group), C. maushomi sp. nov. (C. consors group) and C. bezdeki sp. nov. (C. irinus group). Habitus and male genitalia are illustrated for all Copelatus species from Maharashtra, a key to the species and distribution maps are presented. New distributional records along with short diagnoses of already known species are provided. In addition, the study of extensive material of Copelatus species from the Indian subcontinent outside Maharashtra revealed the following new synonymies: Copelatus freudei Guignot, 1955 = C. gibsoni Vazirani, 1974 syn. nov. = C. gibsoni Vazirani, 1975 syn. nov. = C. spangleri Vazirani, 1974 syn. nov. = C. spangleri Vazirani, 1975 syn. nov.; Copelatus oblitus Sharp, 1882 = C. karnatakus Holmen & Vazirani, 1990 syn. nov.; C. sociennus J. Balfour-Browne, 1952 = C. bangalorensis Vazirani, 1970 syn. nov.; Copelatus tenebrosus Régimbart, 1880 = C. ceylonicus Vazirani, 1969 syn. nov. = C. assamensis Vazirani, 1970 syn. nov.